POSITIONING RACE AT THE CENTRE OF LEGAL DISCOURSE IN POST-APARTHEID SOUTH AFRICA: DISSECTING CLIFF V ELECTRONIC MEDIA (PTY) LTD AND THE LAND REFORM CRISIS (The Pretoria Student Law Review, 2021)
In this paper, I critique the manner in which law rationalises Black subordination and white supremacy through its assumption of racial neutrality and ontological equality.4 I seek to postulate the need for a culture of critique within South African jurisprudence and further challenge hegemonic liberal notions of ‘justice’ and the existing ‘reconciliation’ discourse. The calls for a ‘race conscious’ and general jurisprudence shall be advanced through the epistemological paradigm of Critical Race Theory which offers a politicised account of the law through the acknowledgment of the centrality of race in law and through debunking claims of law’s neutrality and objectivity.5
Keywords: Black subordination; white supremacy; racial neutrality; ontological equality; culture of critique; South African jurisprudence; Critical Race Theory